Increasing the Excellence of Pesantren in Digital era: The Study of Management information System Development at Pondok Modern Darussalam Gontor - Muhammad Akrimul Hakim (TSAQAFAH, 2022)
Abstract: As one of the oldest islamic educational institutions in Indonesia, Pondok Modern Darussalam Gontor (PMDG) continues to improve in order to enhance the education management process, both at the secondary and higher education levels. In this regard, PMDG continues to boost and encourage the maximization of digital technology in the development of management information systems for educational purposes. In an effort to take advantage of technological developments to improve education management, PMDG has adopted a number of policies, including maximizing digital facilities for paying monthly fees and registration fees for new students (digital payments). In the university environment, Darussalam University (UNIDA) Gontor has also used hybrid learning methods during the recent pandemic; online (in the network) and offline (off the network/face to face) simultaneously. Not only in the campus area, PMDG also continues to expand to spread its educational values through its media networks such as websites, print media, online media and social media, such as Instagram and Youtube. This research uses a qualitative approach with descriptive-analytical literature study method. At the end of the discussion, this study tries to explain how information technology systems play an important role in helping various programs to maximize learning process in the environment  of PMDG.